Response of plant functional traits during the restoration of calcareous grasslands from forest stands. (January 2015) - Piqueray, Julien; Ferroni, Lucia; Delescaille, Louis-Marie; Speranza, Maria; Mahy, Grégory; Poschlod, Peter
Abstract: In this survey, we studied the response of plant functional traits to calcareous grassland restoration in the Calestienne region, Southern Belgium (restoration protocol: forest clear-cutting followed by grazing at all sites). We considered traits related to dispersal, establishment, and persistence that integrate the main challenges of plants to re-establish and survive in restored areas. Functional traits were compiled from databases and compared among (i) pre-restoration and young restoration forests; (ii) restoration areas of different ages; and (iii) old restorations and reference grasslands. The following questions were addressed: (i) What is the early response (2–4 years) in terms of plant functional trait following one restorative clear-cut event? (ii) What plants functional trait responses occur from restorative management ( i.e., sheep and goat grazing)? (iii) Which differences still persist between the oldest restored parcels (10–15 years), and the historical reference grasslands? Forest clear-cuts induced several changes among functional traits, including decreased mean seed mass and certain vegetative traits ( i.e., decreased phanerophytes, branching species; and increased short lifespan species i.e., annuals and biennials). During restorative management, clonal, epizoochorous and autumn germinating species were favored. Despite numerous other changes during this phase, many differences remained compared to reference grasslands. In particular, geophytes, mycorrhizal and evergreen species abundance were not approaching reference grassland values. The observed pattern helped to draw inferences on the possible mechanisms operating under vegetation recovery following restorative forest clear-cut and subsequent management were identified and described in this study. Results indicated grazing was an important factor, which increased epizoochorous species, and autumn germinating taxa that filled niches in vegetation opened by summer grazing animals. Finally, differences between old restoration and reference grasslands emphasized that management should focus on reduction in soil fertility, and geophyte rhizomatous grasses. Long-term monitoring is vital to assess if management plans are effective in the complete restoration of species functional trait assemblages.